ショウワ キチ ニオケル オゾン ゼンリョウ カンソク ダイ1カイ ナンキョク キスイケン シンポジウム - 酒井, 重典; サカイ, シゲノリ; SAKAI, Shigenori (国立極地研究所, 1979)
P(論文) 昭和基地におけるオゾソ全量観測は,1961年に第5次越冬隊によって開始された.その後はほかの気象要素とともにほぼ連続して実施されてきた.使用した測器はDobsonオゾン分光光度計である.ここでは,これまでのデータを使い昭和基地におけるオゾン全量の季節変化,観測開始以来の経年変化およびオゾン全量と上層の気温との関連を調べ,その概要を述べる.季節変化は春から夏の初めにかけて最大となり,冬の初めに最小となる.経年変化は1966年以来,ほぼ一定か,わずかな減少傾向を示す.オゾン全量と上層の気温との関連は,10月から12月にかけての期間は特に密接で,この期間の平均気温の経年変化はオゾン全量の変化とまったく一致し,オゾン全量の多い年は気温も高く,オゾン全量が少ない年には気温も下降している. The total ozone amount observations at Syowa Station (69°00'S, 39゜35'E) have been carried out since 1961 by the members of the Japanese Antarctic Research Expedition using the Dobson ozone spectrophotometer. This paper describes general results of annual and year-to-year variations of the total ozone amount, and some statistical relationships between the total ozone amount and the upper level temperature (at levels of 30, 50, 100, 200 and 500 mb). The annual variation of the total ozone amount shows maximum value in spring (November) and minimum value in early winter (June-July). The trend of the total ozone amount since 1966 is almost constant with a slight decrease There is a high correlation between the total ozone amount and the air temperature at 50 and 100 mb levels in October and November departmental bulletin paper